Beyond Reprimand: Performance Counseling as a Humanistic Strategy for Civil Servants at Satpol PP Medan City - Syaiful Anwar Nasution; Tengku Irmayani; Hatta Ridho (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examined the implementation of performance counseling as a developmental, non-punitive strategy for civil servants (Aparatur Sipil Negara/ASN) who received “Poor” or “Very Poor” performance ratings at the Civil Service Police Unit (Satpol PP) of Medan City, Indonesia, following the issuance of Ministerial Regulation PANRB No. 6 of 2022. A sequential exploratory mixed-methods design was used, prioritizing in-depth interviews, observation, and documentation, supplemented by a descriptive questionnaire distributed to eleven ASN counseling participants through total sampling. The findings showed that counseling was implemented through a structured sequence of performance evaluation, problem identification, counseling sessions, guidance, and follow-up monitoring, facilitated by a professional psychologist and grounded in PermenPANRB No. 6/2022 and Medan Mayoral Regulation No. 49/2021. The intervention produced positive outcomes across organizational culture, work motivation, peer relations, stress reduction, loyalty, self-confidence, and the quality of public service delivery; nearly all participants perceived a tangible improvement in their performance. Success was shaped jointly by employees' willingness to change, leadership commitment, and counselor competence. The study concludes that performance counseling functions as a humanistic alternative to administrative punishment and recommends sustained monitoring, stronger leadership involvement, and continued institutional support for ASN counseling programs.